Sturgeon Aquaculture--Specialized Techniques: Determining the Sex of Sturgeon by Direct Examination of the Gonad Using a Minimally Invasive Surgical Procedure - Frank A. Chapman; Joel P. Van Eenennaam (EDIS)
Because male sturgeon are harvested for meat at 2-4 years of age and females are retained for caviar production, being able to determine the sex of individual sturgeon has specific economical advantages. But it is difficult to tell females from males, especially when the fish are young (from hatch to 3 years old). This 5-page fact sheet describes the standard method and tools for determining the sex of sturgeon by direct examination of the gonad using a minimally invasive surgical procedure. Written by Frank A. Chapman and Joel P. Van Eenennaam, and published by the UF Department of Fisheries and Aquatic Sciences, November 2012.